1999
DOI: 10.1007/s11661-999-0275-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of size and shape of tungsten particles on dynamic torsional properties in tungsten heavy alloys

Abstract: The effect of the size and shape of tungsten particles on dynamic torsional properties in tungsten heavy alloys was investigated. Dynamic torsional tests were conducted on seven tungsten alloy specimens, four of which were fabricated by repeated sintering, using a torsional Kolsky bar, and then the test results were compared via microstructure, mechanical properties, adiabatic shear banding, and deformation and fracture mode. The size of tungsten particles and their hardness were increased as sintering tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…This is because the cleavage planes of the tungsten fibers, which have a bcc structure, are {100} planes that consume the least plastic energy at the crack initiation. [24] Kim et al [25] investigated the crack initiation and propagation behavior of tungsten particles by in-situ SEM fracture tests of tungsten heavy alloys, and observed the formation of cleavage facets at almost 90 deg to each other. Inside the tungsten fibers of the present composite, cracks are often formed at about 90 deg, and are observable as secondary cracks on tensile fracture surfaces (Figure 7(c)).…”
Section: B Fracture Mechanisms Of Tungsten-fiber-reinforced Amorphoumentioning
confidence: 99%
“…This is because the cleavage planes of the tungsten fibers, which have a bcc structure, are {100} planes that consume the least plastic energy at the crack initiation. [24] Kim et al [25] investigated the crack initiation and propagation behavior of tungsten particles by in-situ SEM fracture tests of tungsten heavy alloys, and observed the formation of cleavage facets at almost 90 deg to each other. Inside the tungsten fibers of the present composite, cracks are often formed at about 90 deg, and are observable as secondary cracks on tensile fracture surfaces (Figure 7(c)).…”
Section: B Fracture Mechanisms Of Tungsten-fiber-reinforced Amorphoumentioning
confidence: 99%
“…They found that the compressive flow stress of this tungsten heavy alloy increases with the increasing of strain rates from 10 −4 s −1 up to about 7.0 × 10 3 s −1 . Kim et al [10][11] studied the effect of the size and shape of tungsten particles on dynamic torsional properties in tungsten heavy alloys and reported that the size of tungsten particles and their hardness were increased as sintering temperature and time were increased and there would be an appropriate tungsten particle size because the cleavage fracture mode would be beneficial for the "self-sharpening" of the tungsten heavy alloys.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] The desired materials should have a propensity for localized adiabatic shear instability and thus be able to replicate the self-sharpening behavior of depleted uranium (DU) KE penetrators. [1][2][3][4][5] The desired materials should have a propensity for localized adiabatic shear instability and thus be able to replicate the self-sharpening behavior of depleted uranium (DU) KE penetrators.…”
Section: Introductionmentioning
confidence: 99%